Generation and characterization of a functional human adipose‐derived multipotent mesenchymal stromal cell line. Issue 6 (1st March 2019) - Burk, Janina; Holland, Heidrun; Lauermann, Anne F.; May, Tobias; Siedlaczek, Philipp; Charwat, Verena; Kasper, Cornelia
Abstract: Multipotent mesenchymal stromal cells (MSC) and MSC‐derived products have emerged as promising therapeutic tools. To fully exploit their potential, further mechanistic studies are still necessary and bioprocessing needs to be optimized, which requires an abundant supply of functional MSC for basic research. To address this need, here we used a novel technology to establish a human adipose‐derived MSC line with functional characteristics representative of primary MSC. Primary MSC were isolated and subjected to lentiviral transduction with a library of expansion genes. Clonal cell lines were generated and evaluated on the basis of their morphology, immunophenotype, and proliferation potential. One clone (K5 iMSC) was then selected for further characterization. This clone had integrated a specific transgene combination including genes involved in stemness and maintenance of adult stem cells. Favorably, the K5 iMSC showed cell characteristics resembling juvenile MSC, as they displayed a shorter cell length and enhanced migration and proliferation compared with the non‐immortalized original primary MSC ( p  < 0.05). Still, their immunophenotype and differentiation potential corresponded to the original primary MSC and the MSC definition criteria, and cytogenetic analyses revealed no clonal aberrations. We conclude that the technology used is applicable to generate functional MSC lines for basic research and possible future bioprocessing applications. Abstract : The authors generated adipose‐derived multipotent mesenchymal stromal cell (MSC) lines using a library of expansion genes.The selected K5 iMSC clone displayed cell characteristics resembling juvenile primary MSC, thus the technology is useful for the generation of functional MSC lines for basic research and possible bioprocessing applications.